Analysis of Digital Terrain Model from LiDAR Data Using Hydro Enforcement Method on Aquatic Object in SEZ Tanjung Lesung - Febriana, Elisya; Cahyono, Agung Budi (IPTEK Journal of Proceedings Series, 2019)
LiDAR (Light Detection and Ranging) is an active remote sensing system using a laser beam that can generate information about ground topographic characteristics in a horizontal and vertical position. In Indonesia it is still rare to use green waves in LiDAR data retrieval, so the infrared wave generates a value the point cloud elevation is refracted because it can not penetrate the depth of the water. In making aquatic objects from LiDAR acquisition results required method to create a surface water is better. One method of making DTM in aquatic area on data processing LiDAR is hydro enforcement. DTM processing using hydro enforcement method starting from draping terrain of aquatic bodies, eliminating mass points in waters up breakline formation for aquatic bodies according to draping results that have intervals between points cloud in the water body is 0.5 meters. Then do the process of macro hydro enforcement on LiDAR processing software. The results of this study indicate the quality of DTM with hydro enforcement method provides smooth and good visualization for planning infrastructure in irrigation works, water gates and providing good detail. However, this hydro enforcement method still lacks in terms of accuracy, so that the elevation of the aquatic bodies can not be used as a benchmark prior to the sampling field data retrieval